Li, La, Ta doped KNN ceramics obtained by RTGG. (3rd October 2018) - Portelles, J.; Fuentes, J.; Gervacio, J.; Ostos, C.; Raymond, O.; Heiras, J.; Cruz, M. P.; Siqueiros, J. M.
Abstract: The results obtained in the study of [(K0.44 Na0.52 Li0.04 )0.97 La0.01 ]Nb0.9 Ta0.1 03 ceramics obtained by solid state sintering from the precursor NaNbO3 synthetized by the reactive templated grain growth (RTGG) technique are presented. X-ray diffraction studies show the coexistence of two crystals phases, orthorhombic and tetragonal, being the last one, the more abundant. Dielectric measurements make evident the effect of La doping through a decrease in the transition temperatures with respect to those reported for undoped KNN (tetragonal-cubic TT-C = 264 °C and orthorhombic -tetragonal TO-T = 90 °C. The maximum value for the dielectric permittivity is surprisingly high at 6800 at room temperature and 1 kHz. Piezoforce microscopy (PFM) shows domain switching areas in response to the applied electric field but also non-switching zones where the polarization is perpendicular to the applied field. Hysteresis obtained by PFM shows the effective piezoelectric coefficient deff = 164 pC N −1 comparable to the best values of PZT and KNN ceramics.